Valuation of Normal Range of Ankle Systolic Blood Pressure in Subjects with Normal Arm Systolic Blood Pressure - Gong, Yi; Cao, Kai-wu; Xu, Jin-song; Li, Ju-xiang; Hong, Kui; Cheng, Xiao-shu; Su, Hai (PloS one, 2015)
This study aimed to establish a normal range for ankle systolic blood pressure (SBP). A total of 948 subjects who had normal brachial SBP (90-139 mmHg) at investigation were enrolled. Supine BP of four limbs was simultaneously measured using four automatic BP measurement devices. The ankle-arm difference (An-a) on SBP of both sides was calculated. Two methods were used for establishing normal range of ankle SBP: the 99% method was decided on the 99% reference range of actual ankle BP, and the An-a method was the sum of An-a and the low or up limits of normal arm SBP (90-139 mmHg). Whether in the right or left side, the ankle SBP was significantly higher than the arm SBP (right: 137.1 ± 16.9 vs 119.7 ± 11.4 mmHg, P<0.05). Based on the 99% method, the normal range of ankle SBP was 94~181 mmHg for the total population, 84~166 mmHg for the young (18-44 y), 107~176 mmHg for the middle-aged(45-59 y) and 113~179 mmHg for the elderly (≥ 60 y) group. As the An-a on SBP was 13 mmHg in the young group and 20 mmHg in both middle-aged and elderly groups, the normal range of ankle SBP on the An-a method was 103-153 mmHg for young and 110-160 mmHg for middle-elderly subjects. A primary reference for normal ankle SBP was suggested as 100-165 mmHg in the young and 110-170 mmHg in the middle-elderly subjects.